2023
DOI: 10.3390/medicina60010011
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy Comparison between Robot-Assisted Dental Implant Placement and Static/Dynamic Computer-Assisted Implant Surgery: A Systematic Review and Meta-Analysis of In Vitro Studies

Saurabh Jain,
Mohammed E. Sayed,
Wael I. Ibraheem
et al.

Abstract: Background and Objectives: The present systematic review and meta-analysis undertake a comparison of studies that examine the accuracy of robot-assisted dental implant placement in relation to static computer-assisted implant surgery (SCAIS), dynamic computer-assisted implant surgery (DCAIS), and freehand procedures. This study aims to provide a comprehensive understanding of the precision of robot-assisted dental implant placement and its comparative efficacy in relation to other placement techniques. Methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 45 publications
0
1
0
Order By: Relevance
“…With the introduction of precise digital machines, dentists can provide high-quality treatment to their patients [1,2]. Various studies have shown that these computer-aided machines help dentists in various ways, from the fabrication of prostheses using CAD/CAM [2][3][4][5] to the use of robots in the treatment of patients [6][7][8]. The introduction of AI has taken dentistry to the next level.…”
Section: Introductionmentioning
confidence: 99%
“…With the introduction of precise digital machines, dentists can provide high-quality treatment to their patients [1,2]. Various studies have shown that these computer-aided machines help dentists in various ways, from the fabrication of prostheses using CAD/CAM [2][3][4][5] to the use of robots in the treatment of patients [6][7][8]. The introduction of AI has taken dentistry to the next level.…”
Section: Introductionmentioning
confidence: 99%